Gallbladder cancer at a tertiary referral hospital in Peru: characteristics and outcomes in 20 years’ experience - De La Cruz Ku, Gabriel (2025)
Objective: Gallbladder cancer is a relatively uncommon neoplasm of the biliary system, characterized by a notably high mortality rate. Thisstudy aimed to identify prognostic factors for overall survival (OS) in Peruvian patients undergoing surgery for gallbladder cancer. Materials and methods: We conducted a retrospective cohortstudy of patientswith gallbladder carcinoma who underwent surgery at the Instituto Nacional de Enfermedades Neoplásicas between 2000 and 2020. OS was analyzed using the Kaplan–Meier method, and prognostic factors were identified using Cox proportional hazardsregressionmodels. Results: A total of 64 patientswere included. Themedian agewas 62 years, and 75%were female.Most patientswere diagnosed at stage T3 (37.5%), and 25% had M1 stage disease. Additionally, 51.6% of tumors were moderately differentiated, and 71.9% were of the adenocarcinoma histologic subtype. With a median follow-up of 70 months, the 3-year OS rate was 45%. Independent prognostic factorsforOS included AJCC stage, high histological grade (vs. well/moderately differentiated; HR = 2.65, 95% CI: 1.06–6.63), and histologic subtype other than adenocarcinoma (HR = 3.10, 95% CI: 1.21–7.99). Conclusions: Prognostic factors associated with worse OS in Peruvian patients with gallbladder cancer undergoing surgery include AJCC stage, poorly differentiated histological grade, and histologic subtypes other than adenocarcinoma.